Comprehensive Assessment of the Impact of Mandatory Community-Based Health Insurance in Burkina Faso - Delphine Boutin; Laurene Petifour; Yvonne Allard; Souleymane Kontoubré; Valéry Ridde (Institute of Labor Economics (IZA), 2024)
Offering health coverage to informal workers and their families is an ongoing and major challenge in most Sub-Saharan countries. As anchoring insurance to employment contracts is not possible and the demand for insurance is too low to deploy voluntarily sustainable schemes, alternative initiatives are needed. Bundling health insurance to microcredit is an option that we evaluate in this paper. We conducted a two-year cluster randomized controlled trial (RCT) to evaluate the impact of a compulsory micro-health insurance scheme integrated into a micro-loan system for informal micro-entrepreneurs in Ouagadougou, Burkina Faso. Our sample comprised 101 microcredit groups of a partner microfinance institution (MFI), among which we surveyed 1200 individuals (mostly female informal workers). The members of the 47 randomly selected treatment groups had to adhere to health insurance to get access to microcredit. In contrast, members of the 54 control groups did not get health insurance. We assessed the impact of subscription to health insurance on financial protection, healthcare utilization, and health out-comes, and estimated both the intention-to-treat effect (ITT) and the local average treatment effect (LATE). We did not identify any selective attrition, therefore there was no rejection of the MFI due to the health insurance product. Our results reveal a significant and positive impact of health insurance on financial protection. Out-of-pocket expenditures are reduced, as are difficulties in paying for healthcare and the adverse effects of healthcare expenses on professional activities. Health insurance encourages respondents to seek care at modern healthcare facilities rather than relying on self-medication and traditional healers. However, we find no significant impact on health outcomes, whether physical or psychological. Compulsory health insurance has the potential to offer financial protection against health risks to MFI members, a population that lacks social protection, without jeopardizing the retention rate of the MFI. It can create incentives for individuals to seek appropriate healthcare when necessary rather than relying on self-medication. However, the potential impacts on health involve indirect and long-term mechanisms, making them challenging to identify.
Keywords: I13; I15; O12; G21; O55; 330; micro health insurance; financial protection; healthcare utilization; Informal sector; Burkina Faso